PERAN PEMUKA MASYARAKAT DALAM MENYELESAIKAN KONFLIK DI GUNUNG JATI KECAMATAN KENDARI BARAT - Lilin Handriani, Bahtiar, dan Hj. Ratna Supiyah (Fakultas Ilmu Sosial dan Ilmu Politik, 2016)
Problems in Research It Is What Community Leaders Role in Resolving Conflict In Gunung Jati subdistrict of West Kendari. This study aims to describe the role of Community Leaders, Local Government And Public Institutions to Address Conflict Inter-group in the Village Gunung Jati And Jati Mekar Village Kendari. This research Located In Village Gunung Jati And Mekar Jati village. This research Implemented With How to Collect Data Through Observation Form Field Research And Depth interview. Results of this study indicate that role of the Government of the District, Public Agencies, as well as The Police's been running as it should be complied with Tasks and Functions of Each For The First In Decision Making and Policy Although Handling Government is still quite weak, Will but in this case the Local Government Neutral Position already without distinction to Each Lain.Untuk resolving the conflict in the Village Gunung Jati And Jati Mekar Village, Village Government And Community Leaders To mediation order for this problem to Achieve Peace Point.